Seamounts: Ecology, Fisheries &Amp; Conservation
DOI: 10.1002/9780470691953.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Seamount Ecosystems and their Fisheries

Abstract: Ecosystem models are one way of implementing an integrated approach to the recovery of heavily depleted systems like those on and over seamounts. We review the three main types of ecosystem models that have been applied in understanding seamounts, their ecology and fisheries; we describe Ecopath-with-Ecosim food web simulation models, agent-based models, and a more complex biogeochemical spatially explicit model (Atlantis). We discuss their capabilities, limitations, uncertainty, advantages and disadvantages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Central to the top-down relaxation hypothesis is the hypothetical existence of a large community of pelagic predators that may opportunistically consume gelatinous plankton, thereby stabilizing their populations [6] , [7] . Although there is increasing evidence that many pelagic fish may occasionally consume gelatinous plankton [11] , and some ecosystem models include tuna and billfish as major consumers of gelatinous plankton [12] , it is a big leap from an occasional-consumption model to the strong top-down control assumed by the top-down relaxation hypothesis. Furthermore, nothing is known about the actual significance of gelatinous plankton in the diet of most pelagic mesopredators and apex predators, and there is hard evidence for massive consumption of gelatinous plankton only for some fishes [7] , [13] , [14] and pelagic sea turtles [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Central to the top-down relaxation hypothesis is the hypothetical existence of a large community of pelagic predators that may opportunistically consume gelatinous plankton, thereby stabilizing their populations [6] , [7] . Although there is increasing evidence that many pelagic fish may occasionally consume gelatinous plankton [11] , and some ecosystem models include tuna and billfish as major consumers of gelatinous plankton [12] , it is a big leap from an occasional-consumption model to the strong top-down control assumed by the top-down relaxation hypothesis. Furthermore, nothing is known about the actual significance of gelatinous plankton in the diet of most pelagic mesopredators and apex predators, and there is hard evidence for massive consumption of gelatinous plankton only for some fishes [7] , [13] , [14] and pelagic sea turtles [15] .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of more location-specific models such as the Globally Applicable Area-Disaggregated General Ecosystem Toolbox ('Gadget': Begley & Howell, 2004); Boreal Migration and Consumption (BorMiCon: Stefánnson & Pálsson, 1998); and the European Regional Seas Ecosystem Model (ERMSEM: Baretta-Bekker & Baretta, 1997). It is, however, worth noting that, at present, no general ecosystem simulation modelling systems other than EwE and, possibly Atlantis, have the capacity of performing an equivalent task to that set out here; reviews may be found in Fulton et al (2007) and Whipple et al (2000).…”
Section: Seafood Sustainability and Krill Harvestmentioning
confidence: 94%
“…The end-to-end modeling approach requires full coverage of ecosystem components, the integration of physical and biological processes at different scales and two-way interaction between ecosystem components (e.g., Fulton et al, 2005Fulton et al, , 2007. End-to-end models attempt to include all major relevant processes in the system (Fig.…”
Section: General Considerationsmentioning
confidence: 99%